TEKNOLOGI PENGOLAHAN GULA COKLAT CAIR NIRA SIWALAN (Borassus flabellifer L.) [Brown Sugar Syrup Processing from Siwalan Palm Saps (Borassus flabellifer L.)] - Nurud Diniyah; Simon Bambang Wijanarko; Hari Purnomo (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2012)
The aims of this research were to find out the effect of different levels of Brix degree in vacuum method to the sugar products and to compare the vacuum evaporation with traditional method (open pan) to the quality of Siwalan sugar products. Randomized Completed Design was used in the first phase of experiment with different levels of Brix content (i.e.60, 65, 70 and 75°Brix), as single factor and each treatment was replicated 6 times. In the second phase of experiment, t-test was used to compare the different methods of cooking techniques, vacuum evaporation and traditional method and each treatment was replicated 10 times. The results showed that in the first phase, 75ºBrix was observed as the optimum product and characterised by 34.55 of brightness (L*), 8.83 of redness (a*), 22.35 of yellowness (b*), 6.63 of pH, 6.99 x 103cPof viscosity, 7.73% of reducing sugar, and organoleptic scoring were 107 for viscosity, 108 for colour, 110 for taste, 98 for aroma. At the second stage, it can be concluded that Siwalan sugar product produced using vacuum method gave a better quality compound to the traditional one (open pan).